2021
DOI: 10.1111/jfbc.13902
|View full text |Cite
|
Sign up to set email alerts
|

Immunity boosting nutraceuticals: Current trends and challenges

Abstract: The immune function of the human body is highly influenced by the dietary intake of certain nutrients and bioactive compounds present in foods. The preventive effects of these bioactive ingredients against various diseases have been well investigated. Functional foods are consumed across various diverse cultures, in some form or the other, which provide benefits greater than the basic nutritional needs. Novel functional foods are being developed using novel bioactive ingredients such as probiotics, polyunsatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 234 publications
(174 reference statements)
1
20
0
Order By: Relevance
“…It was found that a recombinant IL-1 receptor antagonist significantly reduced seizure duration and recurrence [ 34 , 35 , 36 ], as well as incidence of status epilepticus in rodents [ 37 ]. A possible upregulation or downregulation of proinflammatory cytokines, such as IL-6, IL-1β, TNF-α; as well as anti-inflammatory cytokines, such as IL-4, IL-6, IL-10, IL-11, and IL-13, can be mediated by nutraceutical which defined an immune-boosting property of such foods [ 38 ]. Nutritional treatment with low levels of proinflammatory nutrients and high levels of nutrients with anti-inflammatory properties may be conceived against autoimmune and other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a recombinant IL-1 receptor antagonist significantly reduced seizure duration and recurrence [ 34 , 35 , 36 ], as well as incidence of status epilepticus in rodents [ 37 ]. A possible upregulation or downregulation of proinflammatory cytokines, such as IL-6, IL-1β, TNF-α; as well as anti-inflammatory cytokines, such as IL-4, IL-6, IL-10, IL-11, and IL-13, can be mediated by nutraceutical which defined an immune-boosting property of such foods [ 38 ]. Nutritional treatment with low levels of proinflammatory nutrients and high levels of nutrients with anti-inflammatory properties may be conceived against autoimmune and other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…As for immunostimulators, milk proteins and peptides (bovine lactoferrin, lactoperoxidase, serum albumin, β-lactoglobulin, and α-lactalbumin) have been used as effective immune boosters [ 102 ], although the mechanisms underlying this beneficial effect are not completely clear. Furthermore, probiotics (i.e., Lactobacillus and Bifidobacteria ) might improve the immune response, favoring the competition with pathogens for colonization in the gut and maintaining intestinal barrier integrity, thus reducing permeability to a pathogen and its microbial metabolites [ 104 ].…”
Section: Dietary Recommendations For Patients With Post-covid-19 Synd...mentioning
confidence: 99%
“…et al, 2021b ; Chumroenphat, 2021 ). Moreover, previous studies have demonstrated that polysaccharides have low toxicities and no side effects when used for a disease treatment ( Basak and Gokhale, 2022 ). Most polysaccharides can relieve oxidative stress damage ( Liu et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%